Pengaruh Radiasi Sinar Gamma Cobalt-60 Terhadap Sifat Morfologi dan Agronomi Ketiga Varietas Jagung (Zea mays L.) - . Makhziah; . Sukendah; Yonny Koentjoro (Institut Pertanian Bogor, 2017)
Mutation is one of the ways to improve genetic variation in plant breeding so the target traits were more easily obtained. Grains of three varieties of maize (Bisma, Madura local, and Gumarang) were treated with gamma 60cobalt irradiation doses (0, 100, 200, and 300 Gy) before sowing then planted in a split plot randomized block design with three replication, to be evaluated for their morphology and agronomic traits. The Main plot was cultivars and sub plot was gamma radiation rates. There was no interaction between gamma rates and cultivars of maize, but increasing of gamma rates caused decreasing of some traits. Some traits such as plant height and leaves number were decreased significantly when gamma rate increased 100 to 300 Gy as well yield components such as grain weight and grain number per ear. Gamma 200 caused produce more ears than other rates. Bisma exhibited greater performance than Madura and Gumarang both of morphology and agronomic traits.